Acid-mediated prevention of aspartimide formation in solid phase peptide synthesis - Michels, Tillmann; Dölling, Rudolf; Haberkorn, Uwe; Mier, Walter (Organic letters, 2012)
Aspartimide formation is one of the major obstacles that impedes the solid phase synthesis of large peptides and proteins. Until now, no cost-effective strategy to suppress this side reaction has been developed. Here it is demonstrated that addition of small amounts of organic acids to the standard Fmoc cleavage agent piperidine efficiently prevents formation of aspartimide side products. This effect is shown to be virtually independent of the acid strength.